John Gielgud : matinee idol to movie star - Croall, Jonathan (London : Methuen Drama, 2011)
John Gielgud's career of signature acting roles forever changed our interpretation of the classical repertoire and cemented his role as one of the finest and most influential actors of all time.
Includes bibliographical references and index.
Keywords: Gielgud, John, -- 1904-2000.; Actors -- United Kingdom -- Biography